Can net photosynthesis and water relations provide a clue on the forest decline of Quercus suber in North Tunisia? - Lee, S. H.; Woo, S. Y.; Nasr, Z. (African Journal of f Biotechnology, 2011)
Net photosynthesis, sap flow density (SFD) and water use efficiency (WUE) were measured in a Quercus suber forest in north Tunisia in an attempt to explain the forest decline. In general, sap flow was positively related to light intensity and water loss, indicating that high light intensities can increase the SFD up to the saturation point in the cork oak. CO2 assimilation of cork oak in this region was light intensity-dependent. Cork oak showed a general increase in photosynthetic rates with increasing light intensity up to the light saturation point. Increased radiation probably increased the photosynthesis and growth above ground in this area, whereas the below-ground soil had insufficient moisture for uptake through the roots because the high light intensity and temperature induced high evapotranspiration.
Keywords: decline; evaportranspiration; light intensity; Quercus suber; sap flow density; water use efficiency